Exploring the Opinions of Irish Dairy Farmers Regarding Male Dairy Calves - Maher, James W.; Clarke, AnneMarie; Byrne, Andrew W.; Doyle, Rob; Blake, Martin; Barrett, Damien (Frontiers in Veterinary Science, 2021)
Background There has been very little previous research in Ireland on the farmers’ opinions regarding calf welfare issues. Calf welfare, particularly for male dairy calves, has assumed greater importance in Ireland in recent years due, in part, to an increase in the number of dairy cattle over the past decade. The objective of this study was to explore dairy farmers’ views on a broad range of issues related to the expansion in the dairy herd. Methods A survey was developed to capture the views of farmers regarding male dairy calves. The majority of questions were quantitative, and a final open-ended question collected qualitative data. The survey was distributed to approximately 2,900 dairy farmers via text message and 881 responses were received. Results The sample was composed almost entirely of dairy farmers, although approximately 20% also had a beef enterprise on their farm. 58% of the farmers were concerned with the increase in the number of male dairy calves in recent years. The EU’s abolition of milk quotas, the profitability of dairy farming compared to other farm types, and guidance from farm advisors were the three highest ranked drivers behind the increase in the number of male dairy calves. The three highest ranked options for managing the number of male dairy calves were to increase exports, encourage greater use of sexed semen, and improve the beef merit of these calves. 85% of respondents stated that individual farmers had responsibility for making changes to the number of male dairy calves. The main themes arising from analysis of the responses to the open-ended question, seeking any additional comments, were breed, beef price, live exports, and sexed semen. Conclusions Dairy farmers recognised the responsibility they have for making changes in respect of male dairy calves, and many demonstrated a willingness to make changes in this regard. The important role of other stakeholders, particularly suckler (system where reared from calf to beef) farmers, in rearing male dairy calves for beef production was also recognised. However, the issues of who bears the risks and costs associated with greater integration will have to be carefully considered.